A Crimson Rosella for Josephine. (2nd June 2021) - Fishburn, Matthew
Abstract: A hitherto unrecorded engraving, dated 1803, can now be shown to be the first depiction of an Australian Crimson Rosella (Platycercus elegans) made in France. The engraving was made by François Nicolas Martinet, the ornithological specialist famous for his work with the Comte de Buffon. Quite apart from the intrinsic interest of the image, its history sheds light on the earliest phase of the collection of Josephine Bonaparte at Malmaison, her property on the western outskirts of Paris, and the substantial work she was overseeing in the first years of the century, especially in respect of the natural history collections made during the voyage to Australia of Nicolas Baudin in 1800–04. The plate also provides the key to the story of Martinet's final, abandoned publication, a work that was advertised in 1804 but never completed, copies of which are held in the Smithsonian Libraries and Archives and in Trinity College, Hartford, CT .